Stress and primary headaches - Mindfulness-Based Stress Reduction (MBSR) as a novel avenue for treatment - Julia; Sebastian Szopa (Kazimierz Wielki University, 2024)
Introduction: In today's fast-paced life, an increasing number of people are experiencing chronic stress, which negatively impacts our mental and physical health, leading to troublesome conditions such as primary headaches. Faced with this challenge, more individuals are turning their attention to mindfulness techniques as an effective tool for stress management. In light of this, mindfulness, focusing on the awareness of the present moment, emerges as a promising method for preventing and alleviating stress-induced headaches and the resulting aftermath.  Purpose: Offer a comprehensive overview of the current understanding of the efficacy of mindfulness training, particularly Mindfulness-Based Stress Reduction (MBSR), in the prevention and relief of primary headaches and their associated consequences.  Description of the state of knowledge: MBSR demonstrates the potential for effectively coping with stress-induced headaches and their subsequent effects, including disability related to headaches. This category of pain includes conditions like migraine and tension-type headaches. In the clinical trials conducted thus far participants in the MBSR program show noticeable improvement in headache-related disability, self-efficacy, quality of life, catastrophic pain, and depression scores.  Summary: Studies suggest that integrating mindfulness training could present a promising strategy for preventing and reducing the severity of primary headaches and their consequences, by mitigating stress, a crucial factor influencing the onset of these headaches. To validate these promising findings, further randomized, large-scale, placebo-controlled studies are required.